Deep learning-based brain transcriptomic signatures associated with the neuropathological and clinical severity of Alzheimer's disease. Issue 1 (14th December 2021) - Wang, Qi; Chen, Kewei; Su, Yi; Reiman, Eric M.; Dudley, Joel T.; Readhead, Benjamin
Abstract: Brain tissue gene expression from donors with and without Alzheimer's disease has been used to help inform the molecular changes associated with the development and potential treatment of this disorder. Here, we use a deep learning method to analyse RNA-seq data from 1114 brain donors from the Accelerating Medicines Project for Alzheimer's Disease consortium to characterize post-mortem brain transcriptome signatures associated with amyloid-β plaque, tau neurofibrillary tangles and clinical severity in multiple Alzheimer's disease dementia populations. Starting from the cross-sectional data in the Religious Orders Study and Memory and Aging Project cohort ( n = 634), a deep learning framework was built to obtain a trajectory that mirrors Alzheimer's disease progression. A severity index was defined to quantitatively measure the progression based on the trajectory. Network analysis was then carried out to identify key gene (index gene) modules present in the model underlying the progression. Within this data set, severity indexes were found to be very closely correlated with all Alzheimer's disease neuropathology biomarkers ( R ∼ 0.5, P < 1e−11) and global cognitive function ( R = −0.68, P < 2.2e−16). We then applied the model to additional transcriptomic data sets from different brain regions (MAYO, n = 266; Mount Sinai Brain Bank, n = 214), and observed that the model remained significantly predictive ( P < 1e−3) of neuropathology and clinical severity. The index genes that significantly contributed to the model were integrated with Alzheimer's disease co-expression regulatory networks, resolving four discrete gene modules that are implicated in vascular and metabolic dysfunction in different cell types, respectively. Our work demonstrates the generalizability of this signature to frontal and temporal cortex measurements and additional brain donors with Alzheimer's disease, other age-related neurological disorders and controls, and revealed that the transcriptomic network modules contribute to neuropathological and clinical disease severity. This study illustrates the promise of using deep learning methods to analyse heterogeneous omics data and discover potentially targetable molecular networks that can inform the development, treatment and prevention of neurodegenerative diseases like Alzheimer's disease. Abstract : A pseudo-temporal trajectory was derived for Alzheimer's disease progression from brain transcriptome in a large clinical cohort. The numeric index of the progression is highly predictive of neuropathology and clinical severity in independent data sets. Network analysis identified genes enriched in different cell types implicated for Alzheimer's disease's progression. Graphical Abstract: Graphical Abstract